Corneal viscoelasticity is associated with intraocular pressure under physiological baseline: insights from the rheological properties of corneal lenticules - Yang, Xiaonan; Ren, Qi; Kong, Xiangbin; Su, Peng; Liu, Chang; Liu, Quan; Wan, Pengxia (Frontiers in Bioengineering and Biotechnology, 2025)
This study aims to investigate the modulation effect of baseline intraocular pressure (IOP) on corneal viscoelastic modulus within physiological ranges. We collected 48 stromal lenticules from 26 healthy myopic patients undergoing SMILE surgery. Based on biomechanically corrected IOP (bIOP), stratifying the samples into a low-pressure group (bIOP <15 mmHg, n = 15) and a high-pressure group (bIOP ≥15 mmHg, n = 33) according to pre-operative measurements. Each fresh lenticule underwent strain-controlled torsional rheometry at 37 °C (shear strain 1%, angular frequency 0.1–100 rad s-1), recording storage modulus (G′), loss modulus (G″), complex viscosity (η*), and loss factor (tan δ), with elastic modulus (E) calculated from G′. In parallel, in vivo corneal deformation and stiffness parameters were obtained using the Corvis ST. The results showed that viscoelastic parameters increased monotonically with frequency, demonstrating solid-like behavior; in the frequency range of 100–101.5 rad s-1, G′ and E were significantly higher in the high-pressure group compared to the low-pressure group (both p < 0.05), while the log-modulus versus log-frequency slopes showed no significant difference, indicating an upward “stiffness offset” due to elevated bIOP without altering dispersive characteristics. Corvis ST also confirmed that the high-pressure group exhibited smaller deformation amplitudes and higher stiffness parameters. Overall, even within the normal range, elevated baseline IOP results in an upward shift in corneal E without affecting its time-dependent properties, suggesting that corneal stromal rigidity is adaptable to the ocular pressure environment under physiological conditions.